389 The Association between Arousals and Neurochemical Biomarkers Accumulation in Obstructive Sleep Apnea with Low Arousal Threshold. (3rd May 2021) - Liu, Yi-Shin; Tsai, Cheng-Yu; Majumdar, Arnab; Lin, Shang-Yang; Lin, Yin-Tzu; Ho, Shu-Chuan; Cheng, Wun-Hao; Liu, Wen-Te; Wu, Dean; Lee, Hsin-Chien; Kuan, Yi-Chun; Wu, Cheng-Jung; et al.
Abstract: Introduction: Previous studies indicated the accumulation of neurodegenerative protein may be caused by higher Obstructive sleep apnea syndrome (OSAS) severity. However, the association between arousal-related parameters induced by OSAS and the amyloid burden remains unclear. The aim of this study is to investigate the association between arousal threshold (ArTH) and neurochemical protein accumulation in OSAS patients. Methods: Suspected OSAS participants were performed Mini-mental status examination (MMSE) and full-night polysomnography (PSG) in the sleep center of Taipei Medical University Shuang Ho Hospital, Taiwan. On the same morning, the blood samples were obtained from the participants. The concentrations of total Tau (T-Tau) and amyloid beta peptide 42 (Aβ42) were quantified by ultra-sensitive immunomagnetic reduction assays. An overall of 23 participants were enrolled and classified into Low ArTH group (n=12) and High ArTH group (n=11) based on low ArTH criteria. Regarding the statistical methods, for categorical variables and continuous variables, Fisher's exact test and Mann-Whitney U test were performed to investigate the differences between groups, respectively. The associations between biomarkers concentrations and PSG parameters were assessed by Spearman's correlation. Results: Regarding the demographic characteristics in two subgroups, significantly lower body-mass index and OSAS severity were noted in Low ArTH group (p<0.05). The MMSE was in normal range in both groups and had no significant differences in subgroups. For PSG parameters, there were significantly lower desaturation index, AHI and higher spontaneous arousals index in each sleep stage in Low ArTH group (p<0.01). Nevertheless, in the plasma neurochemical biomarkers, Aβ42 and Aβ42 X T-Tau were significantly higher in Low ArTH group (p<0.05). Moreover, in Low ArTH group, T-Tau was positively correlated with respiratory arousals index (r=0.61, p<0.05) and all arousals index (r=0.76, p<0.01), respectively. The positive correlations between Aβ42 X T-Tau and respiratory arousals index (r=0.62, p<0.05), all arousals index (r=0.75, p<0.01) could also be observed. There were no significant correlations noted in High ArTH group. Conclusion: OSAS patients with low ArTH have higher neurochemical biomarker levels. Also, the significantly positive correlations between arousals and biomarkers were observed in that group. Support (if any):